2011
DOI: 10.1128/mcb.05124-11
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Triggers AMPK Activation through Reactive Oxygen Species-Mediated Activation of Calcium Release-Activated Calcium Channels

Abstract: AMP-activated protein kinase (AMPK) is an energy sensor activated by increases in [AMP] or by oxidant stress (reactive oxygen species [ROS]). Hypoxia increases cellular ROSEnergy-dependent cellular processes require ATP, which is derived from mitochondrial oxidative phosphorylation and/or from glycolysis. Conditions that limit the cellular oxygen supply to the point that oxidative metabolism suffers can threaten cell survival because they undermine the ability of the cell to sustain essential ATP-dependent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
290
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(311 citation statements)
references
References 56 publications
(66 reference statements)
18
290
0
3
Order By: Relevance
“…Furthermore, Mungai et al . demonstrated that moderate hypoxia‐induced AMPK activation occurred through a calcium‐mediated pathway and was abolished by knockdown of CaMKKβ, but not LKB1, which suggested that a Ca 2+ /CaMKKβ/AMPK pathway could enhance the ability of mitochondria to protect cells against a more severe insult 67. We hypothesize that, in response to ISO‐induced myocardial ischaemia, VNS stimulates intercellular Ca 2+ release to protect mitochondria and VNS activates a CaMKKβ/AMPK pathway to alleviate myocardial ischaemia through mitochondrial protection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mungai et al . demonstrated that moderate hypoxia‐induced AMPK activation occurred through a calcium‐mediated pathway and was abolished by knockdown of CaMKKβ, but not LKB1, which suggested that a Ca 2+ /CaMKKβ/AMPK pathway could enhance the ability of mitochondria to protect cells against a more severe insult 67. We hypothesize that, in response to ISO‐induced myocardial ischaemia, VNS stimulates intercellular Ca 2+ release to protect mitochondria and VNS activates a CaMKKβ/AMPK pathway to alleviate myocardial ischaemia through mitochondrial protection.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies suggested that this activation is governed by up-regulation of TRP channels [196,197] while others localized the ER as the target-site [198][199][200][201][202].…”
Section: Hypoxia Effects On Soce and Crac/orai Channelsmentioning
confidence: 99%
“…These ROS might be involved in the regulation of cellular glucose metabolism (Liemburg-Apers et al, 2015b). Although still controversial, it has been proposed that ROS and/or changes in redox state might also activate AMPK (Han et al, 2010;Jensen et al, 2008;Mungai et al, 2011;Wu and Wei, 2012;Zmijewski et al, 2010). Using a previously described strategy (Forkink et al, 2015b;Grefte et al, 2015), we quantified the oxidation of the ROS sensor hydroethidium (HEt; Fig.…”
Section: Stimulation Of Glut1-mediated Glucose Uptake By Acute Oxphosmentioning
confidence: 99%